2011
DOI: 10.1371/journal.pone.0023375
|View full text |Cite
|
Sign up to set email alerts
|

Premature Osteoblast Clustering by Enamel Matrix Proteins Induces Osteoblast Differentiation through Up-Regulation of Connexin 43 and N-Cadherin

Abstract: In recent years, enamel matrix derivative (EMD) has garnered much interest in the dental field for its apparent bioactivity that stimulates regeneration of periodontal tissues including periodontal ligament, cementum and alveolar bone. Despite its widespread use, the underlying cellular mechanisms remain unclear and an understanding of its biological interactions could identify new strategies for tissue engineering. Previous in vitro research has demonstrated that EMD promotes premature osteoblast clustering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…In this study, a time-dependant reduction in osteoblast differentiation was observed when cells were left unpassaged from 7 to 28 days following treatment with EMD. Interestingly, we have previously reported that EMD enhances osteoblast differentiation via cell-cell contacts by upregulating osteoblast gap junctional proteins, connexin 43 ( cx43 ) [32]. Gap junctions are aqueous transmembrane channels that connect the cytoplasm of two adjacent cells and allow the diffusion of small molecules with a molecular mass of less than 1 kDa such as small metabolites, ions, and intracellular signaling molecules (calcium, cAMP, and inositol triphosphate) to pass through [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a time-dependant reduction in osteoblast differentiation was observed when cells were left unpassaged from 7 to 28 days following treatment with EMD. Interestingly, we have previously reported that EMD enhances osteoblast differentiation via cell-cell contacts by upregulating osteoblast gap junctional proteins, connexin 43 ( cx43 ) [32]. Gap junctions are aqueous transmembrane channels that connect the cytoplasm of two adjacent cells and allow the diffusion of small molecules with a molecular mass of less than 1 kDa such as small metabolites, ions, and intracellular signaling molecules (calcium, cAMP, and inositol triphosphate) to pass through [57].…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctions are aqueous transmembrane channels that connect the cytoplasm of two adjacent cells and allow the diffusion of small molecules with a molecular mass of less than 1 kDa such as small metabolites, ions, and intracellular signaling molecules (calcium, cAMP, and inositol triphosphate) to pass through [57]. Cx43 molecules are absolutely essential for osteoblast differentiation and function [58][61] and EMD targets their upregulation [32]. The results from the present study may also indicate that cx43 may be implicated in the down-regulation of osteoblast differentiation in response to EMD following cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…For counting the cell number, 4′,6-diamidino-2-phenylindole (DAPI) was applied to visualize the nuclei as previously described [48]. At each time point, the Ti structures were washed with PBS to remove non-attached cells and fixed in 4% formaldehyde for 10 min followed by staining with DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated the osteoconductive activity of EMD, in particular, for human periodontal ligament cells and osteoblastic cell types [13]. EMD enhances osteoblast differentiation and mineralization [14], as well as contributes to multi-lineage differentiation of human periodontal ligament cells [15]. Furthermore, transplantation of induced pluripotent stem cells combined with EMD greatly enhanced periodontal tissue regeneration [16].…”
Section: Introductionmentioning
confidence: 99%